2003
DOI: 10.1007/s00268-003-6841-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Drainage Fluid Amylase Reflect Pancreatic Leakage after Pancreaticoduodenectomy?

Abstract: This study tried to determine if drainage fluid amylase reflects pancreatic leakage after pancreaticoduodenectomy and to determine the factors affecting the drainage amylase level. Patients undergoing pancreaticoduodenectomy were recruited. The drainage amylase was measured from postoperative day (POD) 1 to POD 7. Direct evidence of pancreatic leakage was provided by upper gastrointestinal studies using a water-soluble contrast medium and methylene blue dye in the pancreaticogastrostomy group or by pancreatico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…19 According to this report, drainage fluid total amylase was significantly higher in the group with a soft pancreatic parenchyma than in the group with a hard pancreatic parenchyma on POD 1-7. The results of the current study were similar to that report.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…19 According to this report, drainage fluid total amylase was significantly higher in the group with a soft pancreatic parenchyma than in the group with a hard pancreatic parenchyma on POD 1-7. The results of the current study were similar to that report.…”
Section: Discussionmentioning
confidence: 83%
“…6,13,17 However, to our knowledge, there have been few detailed comparative studies between patients with a soft pancreatic texture and those with a hard pancreatic texture undergoing PD. Shyr et al 19 reported that a soft pancreatic parenchyma was associated significantly with higher drainage fluid amylase levels than a fibrotic pancreas in patients after PD. The aims of this prospective study were to clarify differences in postoperative changes of serum or drainage fluid pancreatic amylase levels and Creactive protein (CRP) levels between patients with a soft pancreatic texture and those with a hard pancreatic texture undergoing PD.…”
Section: Introductionmentioning
confidence: 98%
“…To provide direct evidence of pancreatic anastomosis leakage, upper gastrointestinal studies (oral intake of 2 ml of methylene blue dye plus 200 ml of water) or a fistulogram were performed in cases in which pancreatic leakage were suspected. Pancreatic leakage was defined as a leak of methylene blue dye into a drain or positive fistulogram findings during the postoperative period [4, 22]. Pancreas texture was determined by gross examination and significant fibrotic change by microscopic examination.…”
Section: Methodsmentioning
confidence: 99%
“…Ihre Häufigkeit wird in der Literatur mit 2-38% angegeben. Diese große Spannbreite erklärt sich aus dem ganz unterschiedlichen z. T. sehr eng oder sehr weit gefassten Definitionen der Komplikation "Pankreasleckage" [26].…”
Section: Insuffizienzen Nach Eingriffen Im Biliopankreatischen Bereichunclassified